Oxidative stress-dependent changes in immune responses and cell death in the substantia nigra after ozone exposure in rat - Rivas-Arancibia, Selva; Zimbrón, Luis Fernando Hernández; Rodríguez-Martínez, Erika; Maldonado, Perla D.; Borgonio Pérez, Gabino; Sepúlveda-Parada, María (Frontiers in Aging Neuroscience, 2015)
Parkinson's disease has been associated with the selective loss of neurons in the substantia nigra pars compacta. Increasing evidence suggests that oxidative stress plays a major role. The resulting increase in reactive oxygen species triggers a sequence of events that leads to cell damage, activation of microglia cells and neuroinflammatory responses. Our objective was to study whether chronic exposure to low doses of ozone, which produces oxidative stress itself, induces progressive cell death in conjunction with glial alterations in the substantia nigra. Animals were exposed to an ozone-free air stream (control) or to low doses of ozone for 7, 15, 30, 60, or 90 days. Each group underwent (1) spectrophotometric analysis for protein oxidation; (2) western blot testing for microglia reactivity and nuclear factor kappa B expression levels; and (3) immunohistochemistry for cytochrome c, GFAP, Iba-1, NFkB, and COX-2. Our results indicate that ozone induces an increase in protein oxidation levels, changes in activated astrocytes and microglia, and cell death. NFkB and cytochrome c showed an increase until 30 days of exposure, while cyclooxygenase 2 in the substantia nigra increased from 7 days up to 90 days of repetitive ozone exposure. These results suggest that oxidative stress caused by ozone exposure induces changes in inflammatory responses and progressive cell death in the substantia nigra in rats, which could also be occurring in Parkinson's disease.